Effect of Thermal Variation and Steaming Time on the Rejection Capacity of Plantain (Musa Sapientum L.) at Gbadolite in the Democratic Republic of Congo - Médard, Molongo Mokondande; Gustave, Apilima Ngandoa; Benjami, Dowiya Nzawele; Médard, Songbo Kwedugbu; Gofroid, Monde te-Kazangba (Budapest International Research and Critics University, 2023)
The present study aimed to observe the effect of thermal variation and steaming time on the rejection capacity of plantain at Gbadolite in the Democratic Republic of Congo. The steamer was used to provide dry heat at the buckling scale according to the temperature and duration of steaming under in vitro conditions at the following temperatures and durations: 50°C, 80, 100 and 120°C for 1', 3 and 10'. Oven-dried subjects were set up in 4 randomized complete blocks, each containing 13 treatments: T0: control or non-oven-dried subject; T1: oven-dried reject at 50°C for 1'; T2: oven-dried reject at 50°C for 3'; T3: oven-dried reject at 50°C for 10'; T4: oven-dried reject at 80°C for 1'; T5: oven-dried reject at 80°C for 3'; T6: discharge steamed at 80 °C for 10'; T7: discharge steamed at 100 °C for 1'; T8: discharge steamed at 100 °C for 3'; T9: discharge steamed at 100 °C for 10'; T10: discharge steamed at 120 °C for 1'; T11: reject steamed at 120°C for 3'; T12: reject steamed at 120°C for 10'; 19; 22; 21; 22; 27; 28; 26; 25; 23; 26; 32; 48; 33 rejects per explant were obtained respectively. Thus, the best treatment remains explants steamed at 120° for 3'. In other words, explants should be heat-excited to stimulate rejection and shorten the weaning period.